Pengaruh Sosial Media Engagement dan Brand Awarenes terhadap Keputusan Pembelian pada Produk Skincare Lokal di Instagram - Salsabila Najwa Nasution; Shiva Falaqia Wivi; Elisabeth Nainggolan (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the influence of social media engagement and brand awareness on the purchase decision of local skincare products on Instagram. The study uses a literature review method with a descriptive qualitative approach based on 10 relevant journal articles that discuss social media engagement, brand awareness, and purchase decision in the context of local skincare products. The findings show that social media engagement plays an important role in creating interaction between brands and consumers, which helps increase brand awareness and strengthen consumer purchase decisions. Brand awareness also contributes significantly to purchase decisions because consumers tend to choose products that are more familiar and trusted. However, several studies indicate that the relationship between these variables is not always direct, as it may also be influenced by other factors such as trust, brand engagement, customer loyalty, and content marketing. This suggests that consumer purchase behavior in digital marketing is complex and shaped by multiple interconnected factors. Therefore, Instagram-based marketing strategies should focus on increasing consumer engagement and building strong brand awareness to support purchase decisions for local skincare products.